Industrial Practice Program Evaluation Using the Kirkpatrick Model - Ismawanto, Iqbal; Sutadji, Eddy; Suharmanto, Suharmanto; Nurhadi, Didik (Fakultas Teknik Universitas Negeri Malang, 2020)
The research objective was to evaluate the industrial practice programs using the Kirkpatrick's evaluation model, which focuses on human resource development. This study used a four-levels of the Kirkpatrick evaluation model, namely reaction, learning, behaviour, and results. The research subjects were the students majoring in mechanical engineering at Private Vocational High School Muhammadiyah 1 Kepanjen who had done industrial practices. The data was collected using a questionnaire instrument, test, interview, and documentation. Based on the data analysis, the evaluation of the industrial practice program on the student's reaction aspect using the facilities, material, instructor, time, and infrastructure indicators was in the 'good' category. The pre-test and post-test results in the learning aspect experienced an increase, as indicated by the mean values of 61.83 and 80.83. Behavioural aspects based on changes in work behaviour, skills and knowledge generally underwent significant changes. The results aspect showed the impact of graduate work performance on increasing incomes and positions; the data showed that only a small proportion of graduates get this increase. The school can use the results of this study as input in dealing with various problems and the success of industrial practice programs.